Parasitoids of Parectopa robiniella Clemens and Phyllonorycter robiniellus (Clemens) (Lepidoptera Gracillariidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A list of parasitoids (Diadegma sp., Colastes braconius Haliday, Apanteles circumscriptus (Nees), A. nanus Reinhard, Pnigalio pectinicornis (L.), P. soemius (Walker), Sympiesis acalle (Walker), S. sericeicornis (Nees), Chrysonotomyia sp., Clostoceurs trifasciatus Westwood, Tetrastichus ecus (Walker)) collected in some localities of Lombardia and Toscana (Italy) are reported. The Hymenoptera emerged from Lepidoptera Gracillariidae Parectopa robiniella Clemens and Phyllonorycter robiniellus (Clemens), introduced in Italy from Northern America, respectively, 20 and 2-3 years ago.
Keywords: Parasitoids; Parectopa robiniella; Phyllonorycter robiniellus; Italy